Mangrove ecological restoration guide: Lessons learned - Teutli Hernández, C.; Herrera Silveira, J.A.; Cisneros-de la Cruz, D.J.; Román Cuesta, Rosa María (CIFOR/CINVESTAV-IPN/UNAM-Sisal/PMC, 2020)
The objective of this Guide is to navigate and strengthen the local capacities of anyone interested in recovering mangrove areas. This guide is intended to support the development of proposals, planning, execution and monitoring of mangrove restoration programs. It sets out, beyond specific methodologies, a strategy that includes the integration of social, economic and ecological components in the restoration process.